Коротка інформація про результати досліджень Канівської експедиції - Болтрик, Ю.В.; Карашевич, І.В.; Козюба, В.К.; Кравченко, Е.А. (Археологічні дослідження в Україні, 2010)
The paper briefly informs about the preliminary results of archaeological prospecting in Kaniv Region of Cherkasy Oblast in the area of construction of Kaniv hydroelectric power station. A description of contemporary condition of the known and the newly discovered in 2009 monuments is presented.